Xerostomia: reasons and methods of correction - S. V. Morozova; I. Y. Meytel (Медицинский совет, 2016)
Xerostomia (drymouth) is a state that develops in reduction or stoppage of the saline secretion and is characterized by dryness in the oral cavity. Due to the numerous diseases and states that xerostomia might accompany the issue of therapy of this category of patients is extremely important for medical practitioners of a wide range of specialties: ENT-specialists, dentists, oncologists.